Systemic contact dermatitis due to nickel - Olivia, Taruli; Budianti, Windy Keumala; Agustina, Fitria (Journal of General - Procedural Dermatology and Venereology Indonesia, 2015)
Introduction: Systemic contact dermatitis (SCD) is a systemic reactivation of a previous allergic contact dermatitis. The initial exposure may usually be topical, followed by oral, intravenous or inhalation exposure leading to a systemic hypersensitivity reaction. A case of a 27 year-old male with SCD due to nickel is reported Case Report: A 27 year-old male presented with recurrent pruritic eruption consist of deep seated vesicles on both palmar and left plantar since 6 months before admission. This complaint began after patient consumed excessive amounts of chocolate, canned food, and beans. The patient worked as a technician in a food factory. History of allergy due to nickel was acknowledged since childhood. The clinical presentation was diffuse deep seated vesicles, and multiple erythematous macules to plaques, with collarette scale. Patch test using the European standard showed a +3 result to nickel. The patient was diagnosed as systemic contact dermatitis due to nickel. The treatments were topical corticosteroid and patient education of avoidance of both contact and systemic exposure to nickel. The patient showed clinical improvement after 2 weeks. Discussion: SCD was diagnosed due to the history of massive consumption of food containing nickel in a patient who had initial sensitization to nickel, with clinical features and the patch test result. Advice to be aware of nickel and its avoidance is important in SCD management.